40+ Full-Text Academic Theses (Ph.D. and M.A.) on Victims of Terrorism, written in English between 2003 and 2021 - McDonald, Broderick (Perspectives on terrorism, 2022)
This bibliography contains doctoral dissertations (Ph.D.) and Master theses (M.A.) on victims of terrorism. Titles were retrieved manually by searching the Open Access Theses and Dissertations Database (OATD), using various combinations of search terms, including - but not limited to - ‘Victims of Terrorism’, ‘Fatalities’, ‘Terrorism’, ‘Violent Extremism’. More than 220 entries were evaluated, of which 41 were ultimately selected for this list. All theses are open source. However, readers accessing them should observe possible copyright restrictions. The title entries below are hyperlinked, or ‘clickable’, allowing access to full texts.